The Voice of Teachers Involved in School-Work Alternance Programmes - Concetta Tino (Firenze University Press, 2018)
Data from Censis 2011 highlighted worrying aspects of school dropouts (18%) and a NEET population increase (22.1%); the same elements were also highlighted by data from Cedefop (2014), where the issue of youth unemployment (21.7%) was also mentioned. In addition to this are the disappointing results from OCSE-Pisa surveys demonstrating that Italian educational institutions fail to provide young people with the skills they need to effectively solve real-life problems. In this scenario, at an Italian and European level, the importance of solving these problems is repeatedly underlined, with the creation of instruments to interconnect the world of education and the world of work. Within this process, School-Work Alternance (SWA) programmes can find a place. This study focuses on the strategic action of their key actors in creating effective partnerships with external organizations. Based on this assumption, the research question asked was: what specific functions do teachers play within School-Work Alternance programmes? Methodology: a qualitative methodological approach was used; data were collected through semi-structured interviews addressed to 14 high school teachers, and subsequently analysed using Atlas.ti software in order to record the significant core categories that emerged. Results: the data collected showed that within the SWA system yet to be defined, SWA teacher/tutors and coordinators in school contexts have played a significant role within School-Work Alternance programmes to date. Final remarks: teachers involved in School-Work Alternance programmes have a strategic position. These results have some practical implications at both educational/training and professional levels
Keywords: school-work alternance programmes; activity theory; boundary objects; training; boundary crossers